Photospheric Radius Expansion and a Double-peaked Type-I X-Ray Burst from GRS 1741.9-2853 - Pike, Sean N.; Harrison, Fiona A.; Tomsick, John A.; Bachetti, Matteo; Buisson, Douglas J. K.; Garcia, Javier A.; Jiang, Jiachen; Ludlam, R. M.; Madsen, Kristin K. (Astrophysical Journal, 2021)
We present an analysis of two type-I X-ray bursts observed by NuSTAR originating from the very faint transient neutron star (NS) low-mass X-ray binary GRS 1741.9-2853 during a period of outburst in 2020 May. We show that the persistent emission can be modeled as an absorbed, Comptonized blackbody in addition to Fe K alpha emission, which can be attributed to relativistic disk reflection. We measure a persistent bolometric, unabsorbed luminosity of L-bol=7.03(-0.05)(+0.04) x 10(36) erg s(-1) , assuming a distance of 7 kpc, corresponding to an Eddington ratio of 4.5%. This persistent luminosity combined with light-curve analysis leads us to infer that the bursts were the result of pure He burning rather than mixed H/He burning. Time-resolved spectroscopy reveals that the bolometric flux of the first burst exhibits a double-peaked structure, placing the source within a small population of accreting NSs that exhibit multiple-peaked type-I X-ray bursts. We find that the second, brighter burst shows evidence for photospheric radius expansion (PRE) and that at its peak, this PRE event had an unabsorbed bolometric flux of F-peak = 2.94(-0.26)(+0.28) x 10(-8) erg cm(-2)s(-1) d = 9.0 +/- 0.5 kpc, assuming that this corresponds to the Eddington limit for pure He burning on the surface of a canonical NS. Additionally, we performed a detailed timing analysis that failed to find evidence for quasi-periodic oscillations or burst oscillations, and we place an upper limit of 16% on the rms variability around 589 Hz, the frequency at which oscillations have previously been reported.
CRIS-Team WoS Importer:2021-09-03